Serum osteoprotegerin levels are related to height loss : the Tromsø Study - Jørgensen, Lone; Hansen, John-Bjarne; Brox, Jan; Mathiesen, Ellisiv B.; Vik, Anders; Jacobsen, Bjarne Koster (European Journal of Epidemiology, 2011)
Severe loss of body height is often a consequence of osteoporotic vertebral fractures. Osteoprotegerin (OPG) and receptor activator of nuclear factor-kB ligand (RANKL) are cytokines essential for the regulation of bone resorption. The aim of this study was to assess the relationship between the OPG/RANKL system and height loss. A total of 4,435 inhabitants from the municipality of Tromsø, Norway (2,169 men and 2,266 women) were followed for 6 years. Baseline measurements included height, weight, bone mineral density, OPG, RANKL,serum parathyroid hormone and information about lifestyle,prevalent diseases and use of medication. Height was measured again at follow-up, and the loss of height was categorized into 4 groups: B1, 1.1–2, 2.1–3,[3 cm. We found increasing height loss with increasing baseline OPG levels in both men and women (P trend = 0.02 and 0.001,respectively), after adjustments for age and other confounders.However, when the women were stratified according to menopausal status and use of hormone replacement therapy (HRT), a significant relationship was present only among postmenopausal women not using HRT (P trend = 0.02). No relations between OPG and height loss were found in post-menopausal HRT-users and premenopausal women (P trend C0.39). We conclude that height loss is positively associated with OPG in men and in postmenopausal women not using HRT. No relationship was found between RANKL and height loss.